PREDICTION TO HYPERTROPHIC FORMS OF GINGIVITIS IN CHILDREN WITH GENETIC ASSESSMENT - Dienga, A.E.; Malekh, N.V.; Verbytska, T.G.; Rozhko, P.D.; Shnaider, S.A. (World of Medicine and Biology, 2022)
The study is dedicated to searching for genetic factors that determine the predisposition to children’s hypertrophic and catarrhal forms of gingivitis. The study involved children with hypertrophic gingivitis (12 patients) and chronic catarrhal gingivitis (16 patients). Because of the study, it was found that hypertrophic gingivitis and chronic catarrhal gingivitis differed significantly in the distribution of polymorphism genotypes TNFRSF1B, MMP1B and TGFB1 in examined patients. No difference was found between the groups by rs1800629 TNF-alpha-308G>A, rs1800795 IL6-174G>C, rs3024491 IL10-1082G>A and rs1800012 COL1A1 IVS1 2046G>T polymorphisms. The results obtained, in our opinion, should be taken into account in the development of treatment and prevention measures to support the dental treatment of children with hypertrophic gingivitis.